Identification of student misconceptions using a four-tier diagnostic test of light matter in Junior High School - Sudirman Sudirman; Hamdi Aksan; Reva Akbarina Irpan (Universitas Sriwijaya, 2024)
This study aims to discover the level of misconceptions about light matter in grade IX students in junior high school. This study uses a quantitative approach and a descriptive method. Data were collected using the Four-Tier Diagnostic Test instrument. The questions used are in the form of multiple-choice questions as many as 15 questions. The subjects of the study were 58 students who had studied light matter. The variable in this study is how the misconception experienced by junior high school students on the light matter is an independent variable, while it will produce the research results which will later become the dependent variable. The results of the study show that many students still experience misconceptions in light materials with an average percentage of misconceptions of 68.39%, not understanding the concept of 15.40%, and understanding the concept of 16.21%. The average percentage of students who experience misconceptions is in the high category. The highest percentage of misconceptions regarding the direction of light propagation with a percentage of 31.03% of students experienced misconceptions in the category of moderate misconceptions.